PERSEPSI MAHASISWA TERHADAP ISU-ISU GENDER DI JURUSAN SENI RUPA MURNI ISI SURAKARTA - Aditya Eko Adrianto; Yuristia Wira Cholifah (Akademi Seni dan Desain Indonesia Surakarta, 2023)
A work of art is the creator’s expression and a medium for conveying a message to the audience. One message that can be voiced is gender. However, the dimensions and issues surrounding gender continue to change, making gender a concept still challenging to understand among university students. This issue is then carried over to the works of art produced by art students. Students tend not to understand gender issues in society. Works of art can be a medium of resistance to breaking narrow views on gender issues. Therefore, this study aims to analyze art students' understanding of gender using Judith Butler's gender theory. This study uses qualitative methods, observation data collection techniques, interviews, and documentation. Four students were selected as informants using the Purposive Sampling technique, with the criteria of students choosing gender as the central theme for their Final Project and having completed the Creation Methodology Course. The study's results show how art students perceive gender issues and how they express or challenge gender issues through art. Keywords: Gender issues, challenge, art students, works of art